The Determinants of Dividend Policy: An Empirical Study of NASDAQ Exchange, NASDAQ Bank Index - Nong, Danni (2014)
This research aims to test the determinants that affect dividend policy for NASDAQ listed banks from year 2006 to 2012. This study mainly focuses on examining three dividend theories of Lintner theory, free cash flow theory and life cycle theory. The data sources for this study are collected from Bloomberg, an online source database. Proxy variables tested are past dividends, current/past earnings, free cash flow over total assets and retained earnings over total equity. General method of moments is used to test impacts of past dividend and current/past earnings on dividends. Random effects model is used to test relationship between free cash flow, maturity of banks and dividend policy. The results demonstrate that NASDAQ listed US banks tend to smooth dividend for each year, and past dividends play a dominant role in influencing current dividends. The analysis further indicates that US banks tend to stable its dividends and try not to cut dividends in order to attract more shareholders’ investment, and during the observation period, number of US banks dividends payers has an upward trend, which may be mainly because under bad economy situation, banks want to use bailed out money to pay dividends to attract more investment and to generate more capital. The results for random effects model indicates that the NASDAQ listed US banks with more excess free cash flow will tend to pay more dividends. But, US banks is not consistent with life cycle theory during 2006 to 2012 that mature banks do not tend to pay more dividends. Thus, the tested significant determinants for dividend policy on US banks are past dividends, current/past earnings and excess free cash flow.